In Memoriam: Prof. Stanislav Andriiovych Iakymenko - Olga Dzhygaliuk (Ukrainian Society of Ophthalmologists, 2023)
Stanislav Andriiovych Iakymenko was born on September 3, 1938, in the village of Ryzhavka, Uman district, Charkasy region. After completing his secondary school education, he entered Bogomolets Kyiv Medical institute in 1955, but in 1957 was transferred to a newly formed Ternopil Medical Institute.